TRAUMATIC BRAINSTEM INJURY DUE TO BLUNT FORCE TRAUMA: AN AUTOPSY CASE REPORT - Wiryaningsih, Made Ayu Mira (Jurnal Forensik dan Medikolegal Indonesia, 2024)
Trauma is the leading cause of morbidity and mortality in patients under 35-years of age and the sixth leading cause of death worldwide, but primary traumatic brainstem injury after blunt force trauma to the head is a rare event. A forensic autopsy was performed on a 35 years old female who was found dead in an apartment building with both her hands and feet tied together and mouth closed with duct tape. External examination showed the victim suffered from blunt force trauma to the head, face, both arms and legs. Internal examination of the body showed hematomas on the scalp, temporal muscles and deep neck muscles and organs, subarachnoid, intraventricular and brainstem haemorrhage and contusion, along with signs of asphyxiation. Trauma to the occipital region of the head not only can cause traumatic brain injury but can also cause trauma to the brainstem as a result from acute hyperflexion of the neck. Haemorrhages and contusions of the brainstem can lead to changes in the respiratory system, depending on the location of the lesions. Cause of death was concluded to be force trauma to the occipital region causing primary brainstem injury with the mechanism of death of asphyxia.